Coexistence of “Cream Skimmer” and “Crumb Picker” Phenotypes in Nature and in Cancer - Huntly, Nancy; Freischel, Audrey R.; Miller, Anna K.; Lloyd, Mark C.; Basanta, David; Brown, Joel S. (Frontiers in Ecology and Evolution, 2021)
Over 50 years ago, seminal papers by Armstrong and McGehee showed how temporal fluctuations in resources or environmental conditions could permit coexistence of two species. Such coexistence results from non-linearities in the way resource supply translates into fitness. These non-linearities reflect trade-offs where one species benefits more than the other during good periods and suffers more (or does less well) than the other during less good periods, be the periods stochastic or seasonal. Since, coexistence based on fluctuating conditions has been explored under the guises of “grazers” and “diggers”, variance partitioning, and as the storage effect. Here we focus on two phenotypes, “cream skimmers” and “crumb pickers”, the former having the advantage under richer times and the latter on less rich times. Examples of coexistence based on fluctuations of resources have been identified in diverse ecosystems in nature. Examples include hummingbirds and bees; large desert rodents versus small; annual versus perennial plants; various intertidal algal feeders, desert annual plants, and plankton; and more. In nature, richer and poorer times, with regular or stochastic appearances, are the norm. These varying fat and lean times occur on many scales of time and space. Rich times and poor times also appear to be the norm in cancer ecosystems. Within tumors, nutrient availability, oxygen, and pH can fluctuate stochastically or periodically, with swings occurring over seconds to minutes to hours. Despite considerable interest in tumor heterogeneity and how it promotes the coexistence of different cancer cell types, the effects of fluctuating resource availability have not yet been explored for cancer. Here, we 1) examine four types of trade-offs that can promote coexistence of phenotypes that do relatively better in richer versus in poorer times, 2) establish that the conditions in tumors are conducive for this mechanism, 3) propose and empirically explore biomarkers indicative of the two phenotypes (HIF-1; GLUT-1; CA IX; CA XII), 4) and compare cream skimmer and crumb picker biology and ecology in nature and cancer to provide cross-disciplinary insights into this interesting, and, we argue, likely very common, mechanism of coexistence.